THE IMAGE OF A TEACHER AS A SOCIO-PSYCHOLOGICAL PHENOMENON (Ideal Journal of Multidisciplinary Research, 2026)
This article examines the external and internal aspects of a teacher’s image, analyzes its components, and reviews the perspectives of scholars on the concept of image. The paper also presents methodological approaches to the effective study of image and provides definitions of the concept proposed by various researchers.
Keywords: image, teacher, impression, worldview, culture, nonverbal communication, verbal communication.